Technology acceptance among oil palm estate workers by using Technology Acceptance Model (TAM) / Norakmal Izzat Azizan - Azizan, Norakmal Izzat (2019)
In the world’s agricultural system, the most organized sector in any country is the oil palm industry included in Malaysia’s oil palm industry. Technology is one of a country’s strategic tools to boost economic competitiveness. Many types of technology have been fictional to helping employees to perform their work method. Malaysia Palm Oil Board (MPOB) introduced many technologies to easy workers work at plantation to improve harvesting productivity. A study was conducted in Jasin, Melaka to investigate the current technology acceptance by using survey and questionnaire method. The purpose of this study are to identify technology usage in oil palm plantation and to investigate the most influence factor that affecting technology acceptance at oil palm plantation. A sample of 80 workers of oil palm plantation took part in the research. The findings show that, behavior has a strongest influence on technology acceptance (β = 0.684) and perceived usefulness and perceived ease to use has a weakness influences a technology acceptance (β = 0.436). The regression result show that 46% variation of technology acceptance can be explain by perceived usefulness and perceived ease to use, attitude and behavior. Oil palm plantation must value the technology and alert with the current situation as the technology nowadays is beneficial to the sector that contain high workload.